Knowledge, Attitudes, and Behaviors of Imams on Prostate Cancer in Kahramanmaras, Turkey - Üçer, Hüseyin; Keten, Hamit Sırrı; Kuş, Celal; Güvenç, Numan; Işık, Oğuz (2022)
Imams are Muslim religious leaders in Turkey, who have a significant influence on society's healthcare attitudes and behavior, and all of them are male. In this study, it is aimed to investigate the knowledge and attitudes of Imams toward prostate cancer (PCa) in order to evaluate their contribution to the fight against PCa in one part of Turkey. This study was carried out on 287 Imams serving in Kahramanmaraş Province in Turkey. A questionnaire investigating the sociodemographic characteristics of the participants and their knowledge, attitudes, and behaviors on PCa was conducted. The mean age of Imams was 40.46 ± 8.93 (min = 22, max = 60). Of the participants, 266 (92.7%) said they had heard of PCa, and 16 (5.6%) had heard of the prostate-specific antigen (PSA) test. The majority of Imam's had poor knowledge regarding PCa. The knowledge score of Imams did not change according to marital status (p = 0.304) or education level (p = 0.16), but the knowledge score significantly increased with age groups (as age increased) (p = 0.010). Results of the present study revealed that Imams lack significant knowledge on PCa. Training on PCa should be organized for Imams, and the issuance of fatwa for PCa should be encouraged. The coordinated work of media, medical personnel, religious officials, and religious schools on PCa will be an important factor in the fight against PCa.
Keywords: Cancer; Imams; Knowledge; Prostate